Molecular characterisation of the globally invasive freshwater crustacean Cherax quadricarinatus (von Martens, 1868) in Zambia - Muyumbana, Namakau; Mudenda, Hangoma; Stelbrink, Björn; Albrecht, Christian; Justus Liebig University Giessen (My University, 2025)
Non-indigenous species are significantly impacting ecosystems, with crayfish becoming a major concern globally. Crayfish are non-native to the African mainland and have been introduced to enhance aquaculture and for ornamental purposes. This study focuses on Cherax quadricarinatus, a crayfish species native to Queensland and the Northern Territory in Australia as well as to southeastern Papua New Guinea, which has established populations in Zambia’s Kafue River and Lake Kariba. We used two mitochondrial markers (COI and 16S rRNA) to assess the haplotype diversity of the two populations and compared these with other non-African populations. Both COI and 16S sequences from Zambia form a major haplotype, which is common throughout the invasive range as well as parts of the native range in Australia. Our data indicates that the widespread haplotype originated from a specific and fairly large source population of Australia that spreads through human-mediated transport. The presence of the species in Zambia raises concerns about the impact of the species on various habitats and competition with native species. Thus, our study emphasizes the need for monitoring and management strategies to prevent further spread of the species in the country and abroad
Keywords: ddc:570